Advances in Human Immune System Mouse Models for Personalized Treg-Based Immunotherapies - Serr, Isabelle; Kral, Maria; Scherm, Martin G.; Daniel, Carolin (Frontiers in Immunology, 2021)
Immunodeficient mice engrafted with a functional human immune system (Human immune system (HIS) mice) have paved the way to major advances for personalized medicine and translation of immune-based therapies. One prerequisite for advancing personalized medicine is modelling the immune system of individuals or disease groups in a preclinical setting. HIS mice engrafted with peripheral blood mononuclear cells have provided fundamental insights in underlying mechanisms guiding immune activation versus regulation in several diseases including cancer. However, the development of Graft-versus-host disease restrains relevant long-term studies in HIS mice. Alternatively, engraftment with hematopoietic stem cells (HSCs) enables mimicking different disease stages, however, low frequencies of HSCs in peripheral blood of adults impede engraftment efficacy. One possibility to overcome those limitations is the use of patient-derived induced pluripotent stem cells (iPSCs) reprogrammed into HSCs, a challenging process which has recently seen major advances. Personalized HIS mice bridge research in mice and human diseases thereby facilitating the translation of immunomodulatory therapies. Regulatory T cells (Tregs) are important mediators of immune suppression and thereby contribute to tumor immune evasion, which has made them a central target for cancer immunotherapies. Importantly, studying Tregs in the human immune system in vivo in HIS mice will help to determine requirements for efficient Treg-targeting. In this review article, we discuss advances on personalized HIS models using reprogrammed iPSCs and review the use of HIS mice to study requirements for efficient targeting of human Tregs for personalized cancer immunotherapies.